Simultaneous Approximation of Sobolev Classes by Piecewise Cubic Hermite Interpolation. Issue 3 (August 2014) - Xu, Guiqiao; Zhang, Zheng
Abstract: For the approximation in L p -norm, we determine the weakly asymptotic orders for the simultaneous approximation errors of Sobolev classes by piecewise cubic Hermite interpolation with equidistant knots. For p = 1, ∞, we obtain its values. By these results we know that for the Sobolev classes, the approximation errors by piecewise cubic Hermite interpolation are weakly equivalent to the corresponding infinite-dimensional Kolmogorov widths. At the same time, the approximation errors of derivatives are weakly equivalent to the corresponding infinite-dimensional Kolmogorov widths.